Web-Based Grape Seed Information System Using the Agile Methodology for the Cikarang Grape Community - Ahmad Turmudi Zy; Bagas Pamungkas; Sunita Dasman; M.Makmun Effendi; Rosa Noviyanti (Politeknik Piksi Ganesha Indonesia, 2024)
This research applies the Agile methodology to develop a web-based grape seed information system for the Cikarang Grape Community. This method was chosen to enhance flexibility and responsiveness in development, with active involvement from community members at every stage. The process begins with a needs analysis through surveys and interviews, followed by an iterative user-focused solution design. Development is conducted in sprints, allowing features to be tested and evaluated regularly. The implementation results show that the system not only improves efficiency in managing and distributing grape seeds but also strengthens cooperation among community members. With transparent and real-time data access, the community is better equipped to make informed decisions regarding production and marketing. This research is expected to serve as a model for future similar information system development.